Work to family, family to work conflicts and work family balance as predictors of job satisfaction of Malaysian academic community. Issue 4 (22nd July 2020) - Rahman, Md. Mizanur; Ali, Noor Azman; Jantan, Amer Hamzah; Mansor, Zuraina Dato'; Rahaman, Md. Saidur
Abstract : Purpose: The purpose of this study is to confirm that work to family conflict (W to FC), family to work conflict (F to WC) and work family balance (WFB) are the predictors of job satisfaction (JS) for Malaysian academic community. To achieve the fundamental objective, the authors first test the direct (structural model) effects of W to FC and F to WC on JS. Secondly, using mediation model, the indirect effects of WFB were calculated through W to FC, F to WC and JS. Design/methodology/approach: Using convenience sampling, the data was collected from 280 academic people who work at private universities in Malaysia. Structural equation modelling technique was applied to complete the data analyses procedures. Findings: The findings revealed that W to FC and F to WC have negative significant effects on JS. Besides, WFB partially mediates only the relationship between W to FC and JS while no mediation effect was found for F to WC and JS. Research limitations/implications: All the research variables in this study were individual-level variables, thus it is suggested to use some organizational and national level variables such as religion and culture as they might be good intervening variables for predicting JS. Practical implications: Using the findings of this research, the Malaysian private universities community can take some necessary initiatives to mitigate work family conflict (W-FC) and ensure WFB and JS that might enhance the standard of higher education in Malaysia. Originality/value: To the best of the authors' knowledge, this is the first attempt to test the mediation effect of WFB in the relationship between both directions of W-FC and JS of employees from the perspective of Malaysia (a collectivist community).